Lead weights of the Selitrennoe settlement: typology and classification - Kazakov Pyotr V.; Pigarev Evgeniy M. (Поволжская археология)
The article deals with the complex of lead mushroom-shaped weights found at different times at the Selitrennoye settlement (Sarai al-Jedid). The collection is represented by 296 pieces of items of various shapes and sizes. The article provides a metrological analysis of products, identifies the design features of weights, which make it possible to determine types and propose their classification. When comparing the available types, the possibility of their division by the place of production (local and imported) is suggested. Also, this paper raises the question of the functional purpose of these subjects; the versions proposed by colleagues on this subject earlier are considered. The materials studied in the article allow us to support the opinion of colleagues about the functional purpose of lead mushroom-shaped items, namely, their use as weights in weaving production.